Pemberdayaan Masyarakat melalui Ergo-entrepreneurship untuk Mengurangi Kelelahan serta Meningkatkan Motivasi Kerja dan Produktivitas Pekerja - Lestari Devi, Ni Luh Putu Mia; Arnita, Ni Putu Sri; Sutajaya, I Made; Adiputra, Luh Made Indah Sri Handari (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2023)
Jaja sengait is a snack that made from sweet potatoes and processed using brown sugar.  Workers cut sweet potatoes using a machine with the help of muscle power with a static working position of ± 2 hours and a long working time of ± 8 hours by carrying out the production process, namely printing hot snacks.  This condition can unwittingly form an unhealthy work culture.  This study aims to apply and prove that community empowerment through Ergo-entrepreneurship can reduce fatigue and increase work motivation and productivity.  This study was a quasi-experimental (quasi-experimental) with the same subject design model (treatment by subject design) and a pre and posttest group design pattern, the assessment was carried out by means of an assessment in the form of: (a) a 30 Items of Rating   Scale questionnaire to determine fatigue indicators;  (b) a work motivation questionnaire is used to collect data on indicators of work motivation;  and (c) hawker products produced during work divided by pulse rate and multiplied by working time.  Data collection was carried out in periods I and II, namely before and after work with a total sample of 15 samples.  The data obtained were analyzed by paired t-test at a significance level of 5%.  The results showed that community empowerment through Ergo-entrepreneurship reduced fatigue by 24.62%, increased work motivation by 63.23%, and increased productivity by 61.58%.  The conclusion in this study is that community empowerment through Ergo-entrepreneurship can reduce fatigue and increase work motivation and productivity of jaja sengait employee.